Estudo de ligas Ti-Nb-Zr e Ti-Nb-Mg, fundidas e na forma de recobrimentos sobre aço inoxidável, para aplicações biomédicas - Cruz, Ernesto David Gonzalez (2019)
In the present thesis, nanostructured coatings of Ti (100 - (20 + z)) -Nb20-Xz alloys (X = Zr and Mg) were produced by sputtering. So with that, it was possible to analyze the effect of the addition of Zr and Mg on the physical, mechanical, morphological, structural and biological behavior compared to the same alloys made by casting in copper mold. The results show that Zr has an effect on the formation of phases, texture, mechanical and biological properties of the TiNb system for both cast alloys and coatings, since low levels favor the formation of martensitic phases regardless of the cooling rate, and in the coatings the precipitation of the ω phase, but for Zr contents greater than 20 at. %, it occurs the stabilization of the β phase. Also, the addition of zirconium causes the presence of texture in the coatings, which is similar to the melted alloys rapidly solidified. In addition, a decrease in both the elastic modulus and the hardness of the cast alloys, reaching values close to the bone with the increase in the cooling rate. While for Mg, the structural, morphological, mechanical and tribological properties depend on the transformation from α to β phase with increasing Mg content. Biologically, the alloys had an increase in cell growth, showing the potential of these systems for their possible use in the manufacture of medical implantation devices.